Studies on anisotropic differences in firmness and sugar content of Huanghwa pear fruit - LU Qiu-jun; WANG Jun; WANG Jian-ping; YU Yong; HU Gui-xian (浙江大学学报. 农业与生命科学版)
Anisotropic differences in fruit firmness and sugar content of Huanghwa pear in relation to ripeness of fruit and location of different parts (including “latitude” and “longitude”) of the fruit was studied. The firmness and sugar content of pear were significantly influenced by “latitude” (top, middle and bottom) and ripeness (least, intermediate and most). Fruit parts corresponding to different “longitudinal” locations showed quite small or no significant differences in the two indices. The distribution of the firmness and sugar content in the pear were analyzed, and the relation between firmness and sugar content were established, and the relation in different ripeness pear were significantly influenced by firmness and sugar content of location of different parts. The better positions to evaluate pear' quality were proposed.